2021
DOI: 10.3389/fimmu.2021.662894
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Versus Late Antiretroviral Treatment Initiation on Naive T Lymphocytes in HIV-1-Infected Children and Adolescents – The-ANRS-EP59-CLEAC Study

Abstract: BackgroundThe early initiation of antiretroviral therapy (ART) in HIV-1-infected infants reduces mortality and prevents early CD4 T-cell loss. However, the impact of early ART on the immune system has not been thoroughly investigated in children over five years of age or adolescents. Here, we describe the levels of naive CD4 and CD8 T lymphocytes (CD4/CD8TN), reflecting the quality of immune reconstitution, as a function of the timing of ART initiation (early (<6 months) versus late (≥24 months of age))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Along with increase in CD4 count, early ART intervention is beneficial for CD8 + T-cells which are a crucial element of the immune system and participate actively to combat viral infections. 22 Saluzzo et al 23 reported that once the patient has acquired HIV, CD4 + tissue-resident memory T cells that are present in the skin get depleted and are replenished only upon early ART initiation. Moreover, WHO has recommended in its 2016 guidelines to start ART for every person living with HIV irrespective of his/her clinical or immunological stage.…”
Section: Discussionmentioning
confidence: 99%
“…Along with increase in CD4 count, early ART intervention is beneficial for CD8 + T-cells which are a crucial element of the immune system and participate actively to combat viral infections. 22 Saluzzo et al 23 reported that once the patient has acquired HIV, CD4 + tissue-resident memory T cells that are present in the skin get depleted and are replenished only upon early ART initiation. Moreover, WHO has recommended in its 2016 guidelines to start ART for every person living with HIV irrespective of his/her clinical or immunological stage.…”
Section: Discussionmentioning
confidence: 99%
“…Whether later ART initiation would result in a similar host responses and rate of TB progression warrants further investigation. Although, early ART has been noted to have beneficial effects on CD8 T cells in HIV-infected children ( 85 ). Our data indicate that early ART initiation provides not only viral control but may also reduce TB severity and mortality in children living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…A study on Children and Adolescents showed that 8% of children did not recover CD4 count >500 after 2 years of therapy (16). This disparity between adults and children might be attributed to the residual thymus function in children and adolescents (39)(40)(41). Additionally, in HIV-infected children, the immune response is notably influenced by Natural Killer (NK) cells.…”
Section: Discussionmentioning
confidence: 99%